Entomopathogenic Exploration Practicum Test For Mustard Fungi in the Laboratory of Biology Students FKIP-UISU 2019 - Azwar, Edi (International Journal for Educational and Vocational Studies, 2019)
Utilization of entomopathogenic fungi as biological control agents is one way to avoid the negative impact of chemicals on the environment. Entomopathogenic fungi that have been widely used for biological pest control are Beauveria bassiana, Metarhizium anisopliae, Aspergillus sp., Nomuraea rileyi. The purpose of this study was to determine the presence of fungi entomopathogenic in the Brassica chinensis vegetable farm, to find out the entomopathogenic characteristics of fungi obtained from each Brassica chinensis planting soil sample, to know the highest entomopathogenic fungi obtained from the exploration of entomopathogenic fungi and to study the results of biology student learning semester VI in microbiology courses. To obtain the entomopathogenic fungi, an exploration technique was carried out using the insect bait Tenebrio molitor placed in the rhizosphere of the Brassica chinensis plant. The preparation in this study involved taking samples from 5 villages in Berastagi, namely Barus Julu, Persadanta, Rumah Rih, Paribun, and Suka Julu by determining 5 diagonal soil sample points. The results of fungi entomopathogenic exploration from 5 villages in Berastagi, there are 3 genus of entomopathogenic fungi in Brassica chinensis rhizosphere, Metarhizium, Beauveria and Aspergillus. The highest fungi entomopathogenic diversity was obtained by Beauveria fungi with a diversity index of 0.3628 while the lowest diversity was obtained by Aspergillus with a diversity index of 0.0343 overall. The results of learning to students indicate that, the ability of students at the time of the pre-test obtained an average value of 59.26 with a standard deviation of 12.8 while at the post-test students obtained an average value of 73.68 with a standard deviation of 8.3 Based on the acquisition of grades on average there is an increase in student learning outcomes in entomopathogenic fungi submateri.